DESCRIPTION OF LEUKOCYT OF SIAM PATIN FISH (Pangasius hypophthalmus) THAT FEED BY ADDITION OF HARUMANIS MANGO SEEDS (Mangifera indica L.) - Syaieba, Mutiara; Lukistyowati, Iesje; Syawal, Henni (Asian Journal of Aquatic Sciences, 2019)
Harumanis mango seed (Mangifera indica L.) is a natural ingredient that can be used as an immunostimulant. The phytochemical content in harumanis mango seeds (M. indica L.) include tannins, flavonoids, saponins and ascorbic acid. This study aims to get the best dose of adding harumanis mango seed solution (M. indica L.) to the feed. The method used was an experimental method with a Completely Randomized Design (CRD) consisting of one factor with four treatment levels which included P0 without the addition of harumanis mango seed solution, P1 addition of harumanis mango seed solution at a dose of 1.6 mL/Kg of feed, P2 addition harumanis mango seed solution at a dose of 1.8 mL/Kg of feed and P3 addition of harumanis mango seed solution at a dose of 2 mL/Kg of feed. Test fish used were Siamese catfish (P. hypophthalmus) measuring 8-12 cm which were kept in cages for 60 days. The results showed that administration of harumanis mango seed solution to feed affected the image of leukocytes of Siamese catfish (P. hypophthalmus) (P < 0,05). The best dose is in the treatment of P3 (2 mL/Kg of feed) with an average total leukocytes 9.76 x 104 cells/mm3, leukocrit levels of 1.67%, lymphocytes 82.00%, neutrophils 7.67%, monocytes 10, 33%, phagocytic activity 31.67% and absolute weight growth of 37.70 g, and 95% survival.